2018
DOI: 10.1002/adom.201701270
|View full text |Cite
|
Sign up to set email alerts
|

The Crucial Role of Charge in Thermoresponsive‐Polymer‐Assisted Reversible Dis/Assembly of Gold Nanoparticles

Abstract: Dynamic control of the spacing between Au nanoparticles using nanoarchitectures incorporating the thermoresponsive polymer poly(N‐isopropylacrylamide) (PNIPAM) has the capability to induce strong color changes from the plasmon shifts. PNIPAM self‐assembles on the surface of Au nanoparticles regardless of its terminal group. However, in many cases, the collapse of this PNIPAM coating at elevated temperatures fails to cause a color change, due to electrostatic and steric repulsion between the Au nanoparticles. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…that demonstrates the crucial role played by salts (e.g., NaCl) in the suspensions of PNIPAM-AuNPs for forming bulk aggregates, i.e., salts bring about charge screening that facilitate nanopartcle aggregation. 24 That study also shows the salts are more effective in inducing the PNIPAM-AuNPs bulk assembly than elevating temperature, a fact consistent with our finding regarding to the aqueous surface assembly of the PNIPAM AuNPs. We show that moderate salt concentrations in 10 nm core diameter AuNPs PNIPAM-AuNPs induce a highly ordered single-layer with in-plane triangular structure, whereas for the 5 nm capped NPs form short range triangular structure that gradually becomes denser as salt concentration increases.…”
Section: Discussionsupporting
confidence: 91%
“…that demonstrates the crucial role played by salts (e.g., NaCl) in the suspensions of PNIPAM-AuNPs for forming bulk aggregates, i.e., salts bring about charge screening that facilitate nanopartcle aggregation. 24 That study also shows the salts are more effective in inducing the PNIPAM-AuNPs bulk assembly than elevating temperature, a fact consistent with our finding regarding to the aqueous surface assembly of the PNIPAM AuNPs. We show that moderate salt concentrations in 10 nm core diameter AuNPs PNIPAM-AuNPs induce a highly ordered single-layer with in-plane triangular structure, whereas for the 5 nm capped NPs form short range triangular structure that gradually becomes denser as salt concentration increases.…”
Section: Discussionsupporting
confidence: 91%
“…The transformation of the extinction spectra of D-g-PNIPAM/AuNPs at a backward decrease in the laser intensity keeps its trend that proves the fact that the laser-induced formation of aggregates of D-g-PNIPAM/AuNPs macromolecules is irreversible. Thus, the present work together with our recent work [30] will show the irreversible character of laser-induced transformations (aggregation) in the Dg-PNIPAM/Ag(Au) NPs hybrids that differ from the temperature-induced transformations which usually are reversible [11][12][13]. Such difference has been rationalized to be a result of the action of attractive optical forces between the Ag NPs that promote the formation of aggregates and counteract their destruction.…”
Section: Introductionmentioning
confidence: 54%
“…Thus, one can conclude that the laser-induced structural transformations in the D-g-PNIPAM/AgNPs hybrid nanosystem is irreversible likely to the transformations in a similar Dg-PNIPAM/AuNPs nanosystem reported in Ref. [30] that is essentially different from the temperatureinduced transformations which are usually reversible [11][12][13]. Thus, it is reasonable to make conclusion of the crucial role of the optical plasmon forces in the aggregation process in the hybrid nanosystems of thermosensitive polymer/metal NPs types.…”
Section: Physical Mechanisms Of Laser-induced Structural Transformatimentioning
confidence: 76%
See 1 more Smart Citation
“…Recently it was demonstrated that gold nanoparticles (NPs) can be reversibly dis/assembled with light using a poly(N-isopropylacrylamide) (pNIPAM) shell. [13,14] The pNIPAM undergoes a lower critical solution temperature (LCST) phase change at T c = 32 °C between a hydrated and dehydrated state. Above 32 °C the pNIPAM shell shrinks as water is expelled and the coating increases in hydrophobicity.…”
mentioning
confidence: 99%